(untitled) (Journal of Energy and Safety Technology (JEST), 2025)
The global shift towards renewable and sustainable energy sources has intensified interest in modern energy harvesting technologies, particularly for low-power electronic applications. However, conventional single-mode energy harvesters, such as standalone piezoelectric nanogenerators (PENGs) or triboelectric nanogenerators (TENGs), face limitations in energy conversion efficiency and consistency under varying mechanical conditions. This study addresses these limitations by proposing a hybrid nanogenerator system that integrates both piezoelectric and triboelectric mechanisms to enhance overall performance. The main objective is to evaluate the energy harvesting efficiency and output characteristics of the hybrid nanogenerator system under different operating scenarios. The hybrid design aims to maximize electrical output and improve system reliability by combining the piezoelectric effect, which converts mechanical stress into electrical energy with the triboelectric effect, which harnesses kinetic energy through contact electrification and electrostatic induction. To achieve this, the system is modeled and simulated using COMSOL Multiphysics and MATLAB Simulink. The PENG component is evaluated based on different materials (PVDF and PZT-5H) and applied mechanical forces, while the TENG component is analyzed under various operational modes (single-electrode and contact-separation). A circuit-level prototype simulation is developed using full-wave bridge rectifier (FWBR) configurations to examine AC-to-DC conversion efficiency and potential for energy storage in lithium-ion batteries. The simulation results reveal that PVDF-based PENGs generate higher voltage output than those made from PZT-5H. For TENGs, the contact-separation mode yields significantly better voltage output than the single-electrode mode. The integration of both nanogenerator types, along with effective rectification, demonstrates the system’s capability to produce stable DC output suitable for powering portable and wearable electronics. This study contributes to the advancement of self-powered technologies by providing valuable insights into the design and optimization of hybrid nanogenerators for practical, scalable energy harvesting solutions.